If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6X + 66 = 8X + -26 Reorder the terms: 66 + 6X = 8X + -26 Reorder the terms: 66 + 6X = -26 + 8X Solving 66 + 6X = -26 + 8X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8X' to each side of the equation. 66 + 6X + -8X = -26 + 8X + -8X Combine like terms: 6X + -8X = -2X 66 + -2X = -26 + 8X + -8X Combine like terms: 8X + -8X = 0 66 + -2X = -26 + 0 66 + -2X = -26 Add '-66' to each side of the equation. 66 + -66 + -2X = -26 + -66 Combine like terms: 66 + -66 = 0 0 + -2X = -26 + -66 -2X = -26 + -66 Combine like terms: -26 + -66 = -92 -2X = -92 Divide each side by '-2'. X = 46 Simplifying X = 46
| 2X+132=8X+90 | | 8X+18=6X+40 | | (-4x^2y)(x^5y^2)=0 | | 2X+130=7X+55 | | 7/x=200/1100 | | -x^2+14x-24= | | 2x-7=9-6x | | 4x-5/x+1=0 | | 8y^2-18y+13=0 | | 9X+168=5X+144 | | (1/4x)-(5/6x)=4-(7/2x) | | 28+18t+2t^2= | | 7t-19=-24+6t | | 16.12=-0.5x^2+0.5x+28 | | 8p-15=-18+7p | | 7-81=p | | (2/(8x+7))=(5/(x+3)) | | 2n=2.5(n-4) | | -3a-5[2a-2[2a-(4a-2)-2(7-3a)]]= | | 6x-10(-2.4)=30 | | (0.75+z)-(z/0.5)=0.25 | | 6-10y=30 | | 5(3+3X)-3=87 | | 5x^2y+75xy-35y= | | 14p-8=21+20p | | 7.8/7.2=x/6 | | 2x-[2x-(-x-(1-x))]= | | 0.7x-0.3x^2+1=0 | | 10x+6(3.333)=30 | | 5x+15=3x-10 | | 5x^7+45x^6+90x^5= | | (7/(x^2-x-12))+(4/(x+3))=(1/(x-4)) |